2002
DOI: 10.1104/pp.010986
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Polygalacturonase in Transgenic Apple Trees Leads to a Range of Novel Phenotypes Involving Changes in Cell Adhesion

Abstract: Polygalacturonases (PGs) cleave runs of unesterified GalUA that form homogalacturonan regions along the backbone of pectin. Homogalacturonan-rich pectin is commonly found in the middle lamella region of the wall where two adjacent cells abut and its integrity is important for cell adhesion. Transgenic apple (Malus domestica Borkh. cv Royal Gala) trees were produced that contained additional copies of a fruit-specific apple PG gene under a constitutive promoter. In contrast to previous studies in transgenic tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
118
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 55 publications
(10 reference statements)
3
118
0
2
Order By: Relevance
“…In a recent study, stomata in leaves of transgenic apple trees overexpressing EPG showed impaired responses to darkness and ABA (21). However, these effects were the result of severe malformation of epidermal and guard cells rather than specific alterations in guard cell wall composition.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, stomata in leaves of transgenic apple trees overexpressing EPG showed impaired responses to darkness and ABA (21). However, these effects were the result of severe malformation of epidermal and guard cells rather than specific alterations in guard cell wall composition.…”
Section: Discussionmentioning
confidence: 99%
“…7E) can profoundly affect the mechanical strength of the cell wall and associated signaling phenomena. An unexpected perspective on the role of pectin in plant development was recently highlighted in transgenic apple (Malus domestica) trees overexpressing an endoPG (Atkinson et al, 2002). The expression of a fungal endoPG in plant tissues reported in this work provides a means to investigate such alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Either up-and down-regulation in tomato of an endogenous gene encoding an endopolygalacturonase involved in fruit softening had no apparent effect on growth and development (Giovannoni et al, 1989;Smith et al, 1990). The expression of a tomato PG in tobacco (Nicotiana tabacum) resulted in no phenotype (Osteryoung et al, 1990), whereas the overexpression of an apple (Malus domestica) fruit PG in apple resulted in novel phenotypes involving changes in cell adhesion (Atkinson et al, 2002).…”
mentioning
confidence: 99%